ANALISIS PERAN PEMERINTAH DESA DALAM MENINGKATKAN KOMPETENSI MASYARAKAT MELALUI PELATIHAN DAN PENGEMBANGAN (Studi Kasus di Desa Manubura Kecamatan Nelle, Kabupaten Sikka) - Yuliana A. Boleng Subah; Nunsio Handrian Meylano; Viktor Eko Transilvanus (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The background of this rescarch has a strstegic rolr in improving community competence through training and development programs. However, the effectiveness of program implementation was often hampered by budget contraints,infrastructure,and minimal.Follow-up. This research aimed to determine the role of the village government,the obstacles faced, and the impact of training on increasing community capacity. The method used in this research was descriptive qualitative with data collection techniques through interviews,observation,and documentation.The data sources used wereprimary and seconday data. The results showed that the village government has made efforts to provide training facilities,conduct socialization, and implement various programs in following local potential,such as agri culture,entrepreneurship,and content creation. Howevwr,program implementation has not been optimal due to budget cnstraints ( the village fun allocation was only around 30% ), a lack of practical facilities, and the absence of continuous assistance and structured evaluation. These conditions have resulted in the impact of training tending to stop at increasing knowledge,which has not yet been fully implemented in the productive economic activities of the community.